Data politics : worlds, subjects, rights - Bigo, Didier; Isin, Engin F. (Engin Fahri), 1959-; Ruppert, Evelyn Sharon, 1959- (Routledge studies in international political sociology, 2019)
"Data has become a social and political issue because of its capacity to reconfigure relationships between states, subjects, and citizens. This book explores how data has acquired such an important capacity and examines how critical interventions in its uses in both theory and practice are possible"--